(untitled) (Scientific journal of the Fergana State University, 2023)
This article presents researches on the specific features of phraseological systems. There are also examples of phraseological systems in English and Uzbek. To identify common features and differences in linguocultural features of phraseological units in the English and Uzbek languages, which include the concepts of "joy" and "sadness". Linguistic description, comparative-typological (comparative), intercultural comparison, conceptual, contextual-situational. Based on component analysis, one of the most common phraseological units in English and Uzbek is a proverb, and in English - an idiom.